Addicted to Facebook? Relationship between Facebook Addiction Disorder, duration of Facebook use and narcissism in an inpatient sample. (March 2019) - Brailovskaia, Julia; Margraf, Jürgen; Köllner, Volker
Highlights: Psychiatric inpatients show increased values of Facebook Addiction Disorder (FAD). They suffer from withdrawal symptoms and interpersonal conflicts due to FAD. FAD level is higher in persons with week depression than with moderate depression. FAD is significantly positively linked to duration of Facebook use and narcissism. Abstract: The present study explored the Facebook Addiction Disorder (FAD) in an inpatient sample in Germany. Of the 112 Facebook users (71.4% women; age(years): M ( SD ) = 49.43 (9.17)), who were patients of a psychosomatic rehabilitation clinic with affective disorders and anxiety disorders as most common diagnoses, 28.6% reached the critical polythetic cutoff score of FAD, 0.9% researched the critical monothetic cutoff score, and 86.6% had enhanced values of withdrawal symptoms due to Facebook use. The mean level of FAD was significantly higher in inpatients with week depression than in inpatients with moderate depression. In the whole sample, FAD was significantly positively linked to duration of Facebook use and the personality trait narcissism. Present results provide first evidence of FAD in a non-student inpatient sample. They contribute to the understanding of the development of FAD and demonstrate that addictive Facebook use may impact persons who suffer from mental disorders, especially when they have enhanced levels of the personality trait narcissism. Practical applications for research and clinical treatment, as well as limitations of present results are discussed.